Consequences of hydrogenated vegetable fat substitution with Ajwa seed oil on physicochemical and nutritional aspects of functional cookies - Raza, Muhammad Qasim (Food Sci Nutr, 2020)
The core objectives of the current study were to explore and compare the proximate and nutritive composition of both types of cookies prepared either with Ajwa seed oil (ASO) or hydrogenated vegetable fat (HVF) and comparative analysis of the antioxidantal potential of both cookies and to reconnoiter the storage effects on the quality parameters of the cookies over a period of 60 days. Outcomes revealed that the cookies prepared with the ASO were superior (p < .05) in fat% and energy as compared to the cookies with HVF. Due to the presence of functional moieties, ASO cookies were found with better palatability, increased shelf life with enhanced physical properties and better functionality. Therefore, the findings of the current study revealed that ASO could be used as an alternative fat source for the preparation of novel functional cookies instead of conventional vegetable fats.